Development of a list of potentially inappropriate medications for patients with heart failure (PIMHF) - Kittipak Jenghua (2020)
© 2020 Elsevier Inc. Background: Several medications are likely to be potentially inappropriate medications for patients with heart failure (PIMHF) as they may worsen heart failure (HF). A screening tool inclusive of PIMHF is lacking. Objective: To develop an extensive list of PIMHF for HF patients. Methods: A list of PIMHF was developed using reviews of recent HF guidelines and literature and validated through a survey study of HF experts using a modified Delphi technique. The study participants were Thai HF experts with ≥ 5 years of practice experience in Thailand. To create an initial list of PIMHF, medications likely to be PIMHF were gathered from both HF guidelines and HF-related explicit criteria. A 3-round Delphi survey was conducted for 9 months, from January 1, 2019 to September 30, 2019. In the first round, medication items that ≥ 60% of the participants rated as “not PIMHF” were excluded. The two subsequent rounds were conducted to measure an agreement on PIMHF. To reach consensus, medication items in the PIMHF list had to meet the following pre-determined criteria: convergence (median ≥ 3.5 and interquartile range ≤ 1.5) and stability (marginal changes of medians between round 2 and round 3 < 15%). Results: Seventeen eligible HF experts, including 10 cardiologists, 3 hospital pharmacists and 4 academic pharmacists, participated in the study. The initial list of PIMHF consisted of 100 medication items. From round 1, 8 medication items were excluded from the initial list. Thus, 92 medication items were considered in the second and the third round, respectively. After 3 surveys, 47 medication items reached the consensus and agreed as PIMHF. Conclusion: This Delphi survey on opinion about PIMHF among an HF expert panel produced a list of 47 medication items as PIMHF which may be used as a screening tool for PIMHF in Thai HF patients.